Interobserver Variability in Assessment of Renal Mass Biopsies - Nyk, Łukasz; Malewski, Wojciech; Kaczmarek, Krystian; Kryst, Piotr; Pyźlak, Michał; Andrychowicz, Aneta; Zabkowski, Tomasz (Urology Journal, 2020)
Purpose: The main goal of this study was to assess the histopathological efficacy of renal mass biopsy and to check the concordance between pathological results and biopsy of the final specimen, as well as interobserver variability in the assessment of biopsy cores. Materials and Methods: A hundred sets of core biopsies of postoperative specimens (renal masses) have been performed. Three core biopsies of the intact specimen had been performed once the kidney with the tumor, or the tumor alone were resected. The urologist aimed to obtain two cores from the peripheral sides of the tumor and one core from its center. The surgical specimen was evaluated by a single pathologist, whereas biopsy samples were referred to three independent pathologists who were blinded to the final results of the renal mass biopsy. Results: Nondiagnostic biopsy rates ranged from 13% to 22%. Sensitivity and specificity ranged 83-97% and 97-99% by excluding nondiagnostic results. The concordance between assessment of surgical specimen and biopsy in the Fuhrman grading system ranged 36.5-77.0%, respectively. Interobserver agreement between the three pathologists was substantial or moderate, depending on the tumor subtype. The Krippendorff's alpha coefficient, calculated by excluding the nondiagnostic results, was 0.28 (moderate agreement) for the Fuhrman grading system. Conclusion: The agreement regarding grading of biopsies between three pathologists ranged from moderate to substantial. Therefore, a team of dedicated uropathologists should be engaged in final diagnosis of renal mass biopsy rather than single one before implementing the proper treatment.